Development in Romania during the post-crisis period: A human, economic and social perspective - Maria-Daniela Tudorache (Theoretical and Applied Economics, 2021)
This paper aims to provide an analysis of the interaction between human, economic and social development in Romania, in the period 2010-2019. To facilitate the examination of the human development, I have used the human development index and its components, while the economic development has been examined using gross domestic product per capita and its determinants. On the other hand, in the case of social development, I have used the poverty rate and other relevant indicators. The conclusion of the paper is that Romania has been on an upward trend in terms of development in the post-crisis period, but further progress are needed to be able to mitigate the development gaps towards the European Union.
Keywords: O11; O15; I32; R11; 330; development; human; economic; growth; poverty